Using theatre in education in a traditional lecture oriented medical curriculum - UZUNER, ARZU; AKMAN, MEHMET; ÇİFÇİLİ, SALİHA SERAP (BIOMED CENTRAL LTD, 2009)
Background: Lectures supported by theatrical performance may enhance learning and be an attractive alternative to traditional lectures. This study describes our experience with using theatre in education for medical students since 2001. Methods: The volunteer students, coached by experienced students, were given a two-week preparation period to write and prepare different dramatized headache scenarios during three supervised meetings. A theatrical performance was followed by a student presentation about history taking and clinical findings in diagnosing headache. Finally, a group discussion led by students dealt with issues raised in the performance. The evaluation of the theatre in education lecture A Primary Care Approach to Headache was based on feedback from students. Results: More than 90% of 43 responding students fully agreed with the statement Theatrical performance made it easier to understand the topic. More than 90% disagreed with the statements Lecture halls were not appropriate for this kind of interaction and Students as teachers were not appropriate. Open-ended questions showed that the lesson was thought of as fun, good and useful by most students. The headache questions in the final exam showed results that were similar to average exam results for other questions. Conclusion: Using theatrical performance in medical education was appreciated by most students and may facilitate learning and enhance empathy and team work communication skills.
Keywords: STUDENTS; ARTS; WIT